On process intensification through storage reactors: A case study on methane steam reforming. (2nd February 2020) - Lowd, John; Tsotsis, Theodore T.; Manousiouthakis, Vasilios I.
Abstract: In this work, the novel storage reactor (SR) process is introduced. A SR consists of two physically distinct domains, designated as the reactor domain and the storage domain, which are allowed to communicate with each other through a semipermeable boundary. It is envisioned that the SR is operated in a dynamic (periodic) manner, that enables the loading and unloading of the storage domain. In this introductory work, a 0-D first principle SR model is developed that quantifies SR dynamic behavior. The resulting governing equations are nondimensionalized, and two dimensionless groups are shown to uniquely determine SR performance, which is quantified through the use of several proposed metrics. An illustrative case study on Steam Methane Reforming is then carried out, involving parametric studies on the two aforementioned dimensionless groups. It is established that the SR outperforms an equivalent Steady-State Reactor (SSR), in regard to the outlined performance criteria